The Impact of the Realistic Mathematics Education Approach on Elementary School Students' Numeracy Skills - Lubis, Azmil Hasan; Aryani, Syifa Defila; Rahmatan, Anzilar (Jurnal Pendidikan Profesi Guru, 2026)
Mathematics is an essential discipline that students must master in order to solve various problems encountered in daily life. One of the competencies that supports the mastery of mathematics is numeracy skills. Several instructional approaches can be implemented to improve students’ numeracy skills, one of which is the Realistic Mathematics Education approach. This study aimed to examine the impact of the Realistic Mathematics Education approach on elementary school students’ numeracy skills in mathematics learning. This research employed a quantitative approach using an experimental method. The experimental design used was a pretest–posttest control group design involving an experimental class and a control class. The population of this study consisted of elementary school students in Banda Aceh, with samples drawn from SD Negeri 16 Banda Aceh and SD Negeri 54 Banda Aceh. The sampling technique used was cluster random sampling. The data were quantitative data obtained through a numeracy test. The collected data were analyzed using descriptive statistics by calculating the mean and standard deviation, and inferential statistics using paired sample t-tests and independent sample t-tests. The results showed that the Realistic Mathematics Education approach had a significant impact on students’ numeracy skills. This finding was indicated by the higher mean score of the experimental class compared to the control class. In addition, the standard deviation of the experimental class was lower than that of the control class, indicating more consistent learning outcomes. The paired sample t-test results showed a significance value of less than 0.05, indicating a significant difference in students’ numeracy skills before and after the treatment. The independent sample t-test results also showed a significance value of less than 0.05, indicating a significant difference between the experimental and control groups. Based on these findings, the Realistic Mathematics Education approach can be used as an alternative instructional approach to strengthen elementary school students’ numeracy skills in mathematics learning.